STOVIA DAN KEHIDUPAN SOSIAL MASYARAKAT DI HINDIA BELANDA - Annisa Nur Hidayah; Ayu Lisda; Denisa Ramadhani (CV Putra Publisher, 2022)
Today education has become a title that is widely used by the wider community to achieve prosperity and happiness in life. Therefore, it is from education that the mindset of a community can be developed to take action for the long term. Education and the education system in Indonesia itself has in fact existed long before the colonialism and imperialism era occurred. At first, education in Indonesia started from a simple one, then developed in religious education until then it was influenced by western education brought by the colonizers. Entering the 20th century in the Dutch East Indies also marked the beginning of an ethical era that included three areas of progress, one of which was education as a form of gratitude and moral responsibility for the treatment of the Dutch Government during the exploitation of the Dutch East Indies (now Indonesia). The purpose of this study is to reconstruct the history of medical schools in Indonesia and their impact on society. This research method uses the historical method with a descriptive qualitative approach which is based on the available data. The results showed that the establishment of the STOVIA Medical School was initiated by the presence of several types of infectious diseases in Indonesia which made the Dutch government overwhelmed in dealing with them. Developments in the field of education during the colonial era have created literacy groups that are considered by the community as Priyayi. At that time, STOVIA had a policy of denying access to higher education for women. Educational opportunities were open, but the Dutch colonial government imposed education costs on women. This is in stark contrast to men who do not pay tuition. Various policies to revitalize the curriculum color the journey of this medical school. STOVIA alumni are well-known as the founders of the momentum for national awakening who have a very high concern for the community. Not a few STOVIA alumni have opened a practice without asking for a penny in return for small communities in need.